A novel pulse multiplication circuit for reducing harmonic distortion of 12 pulse rectifiers in aircraft electrical power systems - Rohollah Abdollahi; Ahmad Salemnia; Morteza Abdolhosseini (IET Electrical Systems in Transportation)
Abstract To improve the performance and reduce the total harmonic distortion (THD) of the autotransformer 12‐pulse rectifier, a novel pulse multiplication circuit (PMC) based on two tapped inter‐phase reactors (TIPRs) is proposed to improve performance and reduce the THD of the autotransformer 12‐pulse rectifier. The proposed rectifier includes a phase‐shifting autotransformer based on a polygon connection, two 6‐pulse diode bridge rectifiers (DBRs), and a PMC. The novel PMC consists of two TIPRs (TIPR1 and TIPR2), an auxiliary single‐phase diode bridge (including four diodes D1 to D4), and two auxiliary diodes D21 and D22, which are connected directly to the output terminal of the DBRs (DBR1 and DBR2). The simulation and experimental results confirm the high capability of the proposed PMC to reduce the harmonic distortion of the input current, so that by using the proposed PMC, the input current is almost sinusoidal and the THD of the input current is less than 3%. Also, the results show that the proposed 12‐pulse rectifier meets the standard requirements of aircraft electrical systems (DO‐160G) without the need for any input and output filters.